E-083 Association of somatosensory evoked potentials and outcome during vasospasm treatment in aneurysmal subarachnoid hemorrhage. (23rd July 2022) - Catapano, J; Naik, A; Scherschinski, L; Winkler, E; Srinivasan, V; Jha, R; JAdhav, A; Albuquerque, F; Lawton, M; Ducruet, A
Abstract : Background: Delayed cerebral ischemia (DCI) and vasospasm is associated high morbidity and mortality in patients with aneurysmal subarachnoid hemorrhage (aSAH). In patients with clinical vasospasm, intra-arterial treatment with vasodilatory medication may be warranted. However, often immediately following treatment the angiographic images remain unchanged and/or only slightly improved. Furthermore, many of these patients are intubated, and a clinical exam may be difficult to assess intra-operatively. Thus, somatosensory evoked potentials (SSEP) during vasospasm treatment may offer rapid assessment if clinical vasospasm is improved and guide whether further treatment is necessary, such as angioplasty and/or additional vasodilatory agents. We therefore analyzed the association of outcomes and SSEP changes during vasospasm treatment in an aSAH patient cohort. Methods: A retrospective analysis of the Post-Barrow Ruptured Aneurysm Trial Database (PBRAT) was performed for all patients treated for an aSAH from 1/1/2014 to 7/31/2019. Inclusion criteria included intra-arterial vasospasm treatment with SSEP monitoring. SSEP monitoring during vasospasm treatment was performed in patients with severe vasospasm in which angioplasty would be considered. Patient demographics, presentation characteristics, intraoperative and post-operative management, and in-hospital and discharge outcomes were abstracted. The primary outcome was improvement in SSEPs associated with clinical improvement. Univariate statistics used Welch's two-sample t-test for continuous data and chi-squared test for frequency-based variables. Results: During the study period, 25 patients met the inclusion criteria. Comparing patients with SSEP improvement (N=9, 36%) vs. non-improvement (N=16, 64%), there were no significant differences in demographic or clinical characteristics including age, sex, BMI, Hunt-Hess and Fisher graddes. In patients with SSEP improvement during the procedure, 5 (56%) were found to have improvement of clinical vasospasm following the procedure compared to only 2 patients (12.5%) in the non-improvement cohort (p=0.064). The duration of vasopressors following the procedure was significantly elevated in patients without improvement (median days: 13.5 (IQR: 5) vs. 3 (IQR: 3), p < 0.001). Greater duration of vasopressor usage was also observed in patients without clinical improvement (median 11.5 (4.75), vs. 4 (7.5), p = 0.015). Discussion: SSEP improvement during angiographic vasospasm treatment is associated with decreased vasopressor requirements. Additionally, a decrease vasopressor usage was observed in all patients with clinical improvement following vasospasm treatment. Larger multicenter studies for the utility of SSEPs during vasospasm treatment is warranted. Disclosures: J. Catapano: None. A. Naik: None. L. Scherschinski: None. E. Winkler: None. V. Srinivasan: None. R. Jha: None. A. JAdhav: None. F. Albuquerque: None. M. Lawton: None. A. Ducruet: None.